2011
DOI: 10.1159/000329337
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain Natriuretic Peptide Levels in Cardiac Function Assessment in Chronic Dialysis Patients

Abstract: Background: Brain natriuretic peptide (BNP) is elevated in patients with end-stage renal disease and could reflect left ventricular dysfunction. Aim: To evaluate the plasma levels of BNP in two groups of asymptomatic patients on different dialysis programs and to correlate their variations with echocardiographic parameters. Methods: Group A consisted of 36 patients on chronic hemodialysis (HD), and group B included 38 patients on continuous ambulatory peritoneal dialysis (CAPD). ECG and echocardiography were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Our results clearly show that patients on HD are more likely to have elevated levels of NT-proBNP compared to patients on CAPD, and this finding may suggest that from the cardiovascular stand point CAPD is a better alternative to HD for renal replacement therapy. These data are consistent with previously mentioned studies [27][28][29] . Whether an advantage predicted by a marker such as NT-proBNP leads to an actual morbidity or mortality benefit cannot be determined from the present study, and this clinically relevant hypothesis warrants further investigation.…”
Section: Abnormal Nt-probnp In Hd Vs Capdsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results clearly show that patients on HD are more likely to have elevated levels of NT-proBNP compared to patients on CAPD, and this finding may suggest that from the cardiovascular stand point CAPD is a better alternative to HD for renal replacement therapy. These data are consistent with previously mentioned studies [27][28][29] . Whether an advantage predicted by a marker such as NT-proBNP leads to an actual morbidity or mortality benefit cannot be determined from the present study, and this clinically relevant hypothesis warrants further investigation.…”
Section: Abnormal Nt-probnp In Hd Vs Capdsupporting
confidence: 94%
“…The thought that such volume shifts would have adverse effect on the cardiovascular system have been postulated before, and there is an accumulating body of evidence suggesting that BNP and NT-proBNP levels are higher among patients on HD (ref. [27][28][29][30]. No previous studies to our knowledge assessed NT-proBNP according to the level of preservation of the left ventricular systolic function.…”
Section: Abnormal Nt-probnp In Hd Vs Capdmentioning
confidence: 99%
“…34 It has also been shown that BNP has a good predictive power for the total and CVD mortality in patients with ESRD. [14][15][16][17]35 Mallamaci et al 16 also showed that cardiac natriuretic peptides, particularly BNP, had a high sensitivity in diagnosing LVH and systolic dysfunction in patients with dialysis. In our study, we found that BNP had a negative correlation with residual diuresis in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8 Many studies have been carried out to discover useful prognostic markers for MHD patients. For instance, blood total homocysteine (tHcy) [9][10][11][12][13] and B-type natriuretic peptide (BNP) [14][15][16][17] have been shown to have good predictive power for the total and cardiovascular disease (CVD) mortality in patients with end-stage renal disease (ESRD). Both tHcy and BNP are useful in identifying LVH or depressed left ventricular systolic function in asymptomatic ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis studies of cardiac biomarkers present conflicting results, with either increasing, decreasing, or stable values post-dialysis as compared to pre-dialysis (16,17,22,33,34) (16,(34)(35)(36)(37)(38)(39). Even when measuring NT-proBNP and BNP in dialysate the results are conflicting (38,40).…”
Section: Introductionmentioning
confidence: 99%